Organic Thermoelectrics: Intrinsic and Extrinsically Limited Thermoelectric Transport within Semiconducting Single‐Walled Carbon Nanotube Networks (Adv. Electron. Mater. 11/2019). (7th November 2019) - Blackburn, Jeffrey L.; Kang, Stephen D.; Roos, MichaelJ.; Norton‐Baker, Brenna; Miller, Elisa M.; Ferguson, Andrew J.
Abstract : In article number 201800910, J. L. Blackburn, A. J. Ferguson, and co‐workers demonstrate two distinct regimes of charge‐carrier transport in doped networks of semiconducting single‐walled carbon nanotubes (s‐SWCNTs). The observation of transport behavior "intrinsic" to the s‐SWCNTs depends on carrier density and the magnitude of "extrinsic" energetic barriers (likely morphological in nature) that limit transport. These results, along with a critical comparison to prototypical semiconducting polymers, suggest that mitigation of extrinsic activation barriers to charge carrier transport is a general design strategy for improving organic thermoelectric material performance. Illustration by Alfred Hicks, NREL.